Urgensi Perampasan Aset Dalam Pemberantasan Korupsi: Dalam Perspektif Hukum Pidana Islam - Al-Kavafi, M. Imdad; Baehaqi, Ja'far; Rosyid, Maskur (Universitas Semarang, 2025)
The effective recovery of assets derived from corruption remains a major challenge within Indonesia’s criminal justice system. The Draft Law on Asset Forfeiture (RUU PA) introduces a non-conviction-based (NCB) mechanism, enabling asset confiscation without a prior conviction of the offender. This study analyzes the normative legitimacy of the NCB approach under Indonesian positive law. It explores its doctrinal foundations from the perspective of Islamic criminal law, specifically through the concepts of ta‘zīr and maqāṣid al-sharī‘ah. Employing a normative-comparative approach, this research demonstrates that the principle of ta‘zīr provides legal justification for asset forfeiture in the pursuit of public welfare, even absent individual penal sentencing. The findings reveal that the NCB mechanism aligns with Islamic legal values, emphasizing substantive justice and the protection of public property. The novelty of this research lies in its integrative proposal to harmonize Islamic criminal principles with the national legal system, thus supporting a fair and effective asset recovery policy. The study also underscores the importance of strict and accountable regulatory safeguards to prevent abuse of power and to ensure the protection of constitutional rights. Pemulihan aset hasil korupsi masih menjadi tantangan serius dalam sistem hukum pidana Indonesia. Rancangan Undang-Undang Perampasan Aset (RUU PA) memperkenalkan pendekatan non-conviction based asset forfeiture (NCB), yang memungkinkan perampasan aset tanpa menunggu putusan pidana terhadap pelaku. Studi ini menganalisis legitimasi normatif pendekatan NCB dalam hukum positif Indonesia serta mengeksplorasi fondasi hukumnya dalam perspektif hukum pidana Islam, khususnya melalui konsep ta‘zīr dan maqāṣid al-sharī‘ah. Dengan pendekatan normatif-komparatif, penelitian ini menunjukkan bahwa prinsip ta‘zīr memberi ruang legitimasi terhadap perampasan aset demi kemaslahatan publik, bahkan tanpa adanya pemidanaan individual. Hasil studi ini memperlihatkan bahwa pendekatan NCB sejalan dengan nilai-nilai hukum Islam yang menekankan keadilan substantif dan perlindungan terhadap harta publik. Kebaruan dari penelitian ini terletak pada tawaran integratif antara prinsip hukum pidana Islam dan sistem hukum nasional dalam mendukung kebijakan perampasan aset secara adil dan efektif. Ditekankan pula pentingnya pengaturan yang ketat dan akuntabel guna mencegah penyalahgunaan wewenang serta menjamin perlindungan hak konstitusional warga negara.